Effects of manual percussion during postural drainage on lung volumes and metabolic status in healthy subjects - Jirakrit Leelarungrayub (2018)
© 2015 Elsevier Ltd. Objective: The aim of this study was to evaluate the influence of manual percussion during three different positions of postural drainage (PD) on lung volumes and metabolic status. Methods: Twenty six healthy volunteers (13 women and 13 men), with a mean age of 20.15 ± 1.17 years, participated. They were randomized into three standard positions of PD (upper, middle, or lower lobes) and given manual percussion at a frequency of 240 times per minute for 5 min. Lung volumes, including tidal volume (TV), inspiratory reserve volume (IRV), expiratory reserve volume (ERV) and vital capacity (VC); and metabolic status, such as oxygen consumption (VO2), carbon dioxide (VCO2), respiratory rate (RR), and minute ventilation (VE) were evaluated. Results: The lung volumes showed no statistical difference in VC or IRV from percussion during PD in all positions, except for the lower lobe, where increased TV and decreased ERV were found when compared to PD alone. Furthermore, percussion during PD of the upper and middle lobes did not affect RR or VE, when compared to PD alone. In addition, percussion during PD of the middle and lower lobes increased VO2and VCO2significantly, when compared to PD alone, but it did not influence PD of the upper lobe. Conclusion: This study indicated that up to 5 min of manual percussion on PD of the upper and middle lobes is safe mostly for lung volumes, RR, and VE, but it should be given with care in PD conditions of the lower lobe.